Analisis Kebutuhan Tenaga Dengan Metode Workload Indicator Staffing Need (Wisn) Pada Instalasi Rekam Medik RSUD Sultan Imanuddin Pangkalanbun - Abdullah, Nur Fadhilah, Ibnu Mardiyoko, SKM., MM (2016)
Medical record management very was of benefit to patient and also hospital as especial source information of patient health. Problem which was often happened that was lack of amount and energy type required, lack of interest (knowledge, skill, attitude and assess) and also ill fund limitation from home so that can't add and take care of the human resource which they require.One of the solutions to overcome it was with Workload Indicator Staffing Need (WISN) method. The purpose of this researchwasto know analyse of energy requirement with workload indicator staffing need (WISN) method at Medical Record InstallationSultan Imanuddin Pangkalanbun Area Public Hospital.This research methodwas descsriptive with study case design. Subyek amount to 14 officer medical records which was divided become 3 unit work that was 7 management officer medical record, 1 officer of health and legal medico information, and also 6 officer of admission and registration, was taken with purposive sampling technique. The data analyse include the reduction data, data presentation and conclusion withdrawal. The analysis result known that work load which must be accounted on an officer medical record enough heavily because no division of specialized task. In working made available to officer at Medical Record Installation equal to 1644/hour/person/year or 274day/person/year or 98640 minute/person/year with work load standard totally equal to 1805254. Diffuseness standard lead the Medical Record Installation equal to 0,10 and standard of diffuseness of executor staff equal to 0,01. So could be concluded that totalizeing energy requirement based on the formula WISN at Medical Record Instalation of Sultan Imanuddin Pangkalan Bun Area Public Hospital was counted 1 person. Key word: Energy Requirement,Workload Indicator Staffing Need (WISN) Method, Medical Record Instalation